2019
DOI: 10.1558/jasr.37306
|View full text |Cite
|
Sign up to set email alerts
|

Silence, Secrecy and Power

Abstract: Religious groups represented over 60% of all institutions appearing before the Australian Royal Commission into Institutional Responses to Child Sexual Abuse. This indicates that there are specific issues pertinent to the institutional cultures and structures of religious groups with regard to the sexual abuse of children. This warrants close investigation and analysis by scholars of religion. The article provides the background and context to the establishment of the Royal Commission, and an overview of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Christian churches have an extremely poor record on the prevention of harm to young people in their care, as is evidenced by the Australian Royal Commission into institutional responses to child sexual abuse (Wright et al, 2017). Key to the failures of the churches was prioritising institutional power and the protection of privilege, instead of listening to the voices of young people who experienced profound trauma (McPhillips, 2018). The data discussed in this article suggests there are some similarities in the conservative Christian attempt to impose harmful discriminatory practices and attitudes toward LGBTQ+ people in Christian schools.…”
Section: Discussionmentioning
confidence: 99%
“…The Christian churches have an extremely poor record on the prevention of harm to young people in their care, as is evidenced by the Australian Royal Commission into institutional responses to child sexual abuse (Wright et al, 2017). Key to the failures of the churches was prioritising institutional power and the protection of privilege, instead of listening to the voices of young people who experienced profound trauma (McPhillips, 2018). The data discussed in this article suggests there are some similarities in the conservative Christian attempt to impose harmful discriminatory practices and attitudes toward LGBTQ+ people in Christian schools.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of these inquiries have been extremely effective in detailing the prevalence and types of violence as well as the specific institutional mechanisms which embedded cultures of gendered violence in everyday religious practices (Salter, 2018). Inquiries and associated research have revealed the devastating impacts of abuse on victims/survivors (Blakemore, Hirte, et al, 2017) and in particular drawn attention to the ongoing sexual physical and psychological abuse against children in religious communities for much of the twentieth century (McPhillips, 2018). More recent research is demonstrating that the abuse of children in larger Christian groups was organised in networks between (mostly) clerical perpetrators and Church leaders and carefully managed to avoid public scrutiny and police detection (Death, 2018).…”
Section: Research On Religion Gender and Violencementioning
confidence: 99%
“…The tragic impact of abuse for individuals and through them our entire society demands nothing less. (Australian Government 2017b, p. 4) The Australian Royal Commission into Institutional Responses to Child Sexual Abuse 1 (2012-2017) was the longest, largest, and highest funded public inquiry into historical institutional child sexual abuse in Australian history (McPhillips 2018a). It is acknowledged as a global landmark inquiry into child sexual abuse and 'laid bare the sobering reality of institutional child sexual abuse and its profoundly negative impact on individuals, families and communities' (Wright et al 2017, p. 1).…”
Section: Introductionmentioning
confidence: 99%